Ontology based semantic interoperability approach in the Internet of Things for healthcare domain. (18th August 2021) - Ahamed, Jameel; Chishti, Mohammad Ahsan
Abstract: Recent years have seen enormous growth in the number of devices connected to the Internet. With such rapid development in the Internet of Things (IoT) domain, data generated by these devices is ever increasing. Data is considered as one of the most crucial entities in the Internet of Things, and this data may be homogeneous as well as heterogeneous in nature. Analysis of homogeneous information is a simple process as this will not involve further processing, but analysis of heterogeneous data is a huge task. The heterogeneous nature of data in IoT based healthcare system, an important application, leads to semantic interoperability, which is the ability of systems to exchange data with definite, shared meaning. Semantic Interoperability expedites data interchange unambiguously irrespective of format and source of data. Therefore, a knowledge-based model is required to integrate heterogeneous data-generating devices to expand the applications of IoT. In this paper, an ontology-based model is proposed and implemented to collect the patient's diverse data using different tools over gateways. Then the generated/collected data is transmitted to the cloud for processing in terms of semantics and structure. This results in a holistic mechanism in the form of an ontology used for the prediction and diagnostics of heart diseases in patients located at distant places by experts based at another location.